Influence of Adult Literacy Education on the Environmental Behaviours of Women - Norris, Erhabor Igbinosa; E.I., Osayande (European Scientific Journal, ESJ, 2017)
The study assessed the influence of adult literacy education on the environmental attitudes and behaviours of women in Edo State. A sample size of 253 respondents were selected using both census sampling to select the 15 adult literacy centers in the state and simple random sampling by balloting to choose the sample for the study. The instrument for the study had a reliability of 0.75 for the attitude subscale and 0.83 for the behaviours subscale. It was observed from the study that the majority of the respondents (57.3%) had a positive attitude towards the environment and their response revealed that they rarely partake in most pro-environmental behaviours. There was a weak positive relationship observed between the respondents’ environmental attitude and their environmental behaviour. Hence the researchers recommended that more emphasis should be placed on implementing adult environmental education in each of the adult literacy centers in Edo State.